En pilotstudie av hästens beteende vid olika boxgrannar och boxdesign - Westman, Viktoria (2011)
SUMMARY The Swedish laws of animal welfare emphasize the social needs of the horse but nothing is said about how to fulfill this. Though there are few studies done in this subject it can be difficult to understand if the needs are fulfilled. The purpose of this study was to learn more about the horse’s social needs in box stable and to increase other people’s knowledge and understanding of the horse behavior to increase the welfare of the stabled horse. The questions where: How does the horse choose to place itself depending on what horse is next to it? How many attempts does the horse do to take contact and nose contact with the horse next to it? How does the box design affect the horse behavior? 22 Eight horses were videotaped during 24 nights. The horses where observed between 6.30 pm to 7 am. The hours between the last feeding in evening of the horses and the first feeding in the morning were taped. Different horses were taped in the boxes with different types of box design that limited the social contact between them. The result showed that the horses used more time to social behavior during the first nights with its new neighbors in the box next to them. There was a difference between the horses that knew each other from before and the horses that was new to them. When the box design limited the horses from social contact the horses did eat significantly more. There were individual differences in the laying behavior between the horses. The older horses had the most frequent observations during the study. Depending on neighbors in the next boxes the horse chose to place itself different in the box. The result can be summarized in these conclusions: The box design affects the behavior and how the horse places itself in the box. This is one aspect of many to consider with stabled horses. The neighbors in the boxes next to the horse affect the horse behavior and how the horse places itself in the box. Therefore it is relevant to try to observe how the horse reacts to the horses next to it and try to place the horses in the stable with purpose to make a stable with a calm and relaxing atmosphere.